2000
DOI: 10.1212/wnl.55.10.1467
|View full text |Cite
|
Sign up to set email alerts
|

A new locus for autosomal dominant nocturnal frontal lobe epilepsy maps to chromosome 1

Abstract: The authors provided evidence for a third locus associated to autosomal dominant nocturnal frontal lobe epilepsy on chromosome 1. Among the known genes mapping within this critical region, the ss2 subunit of the nicotinic receptor (CHRNB2) represents the most obvious candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 30 publications
2
55
0
2
Order By: Relevance
“…The ADNFLE locus ENFL3 was mapped to chromosome 1p21 in a three-generation pedigree from southern Italy (32). The acetylcholine β2 subunit gene had previously been mapped to this location, and molecular analysis identified the amino acid substitution V287L (23).…”
Section: Ligand-gated Acetylcholine Receptorsmentioning
confidence: 99%
“…The ADNFLE locus ENFL3 was mapped to chromosome 1p21 in a three-generation pedigree from southern Italy (32). The acetylcholine β2 subunit gene had previously been mapped to this location, and molecular analysis identified the amino acid substitution V287L (23).…”
Section: Ligand-gated Acetylcholine Receptorsmentioning
confidence: 99%
“…A 'single gene' trait was identified with linkage to chromosome 20q [Phillips et al 1995]. Further gene loci have been linked to chromosomes 15q24 [Phillips et al 1998] and 1q21 [Gambardella et al 2000]. Mutations in two genes encoding different subunits of the neuronal nicotinic acetylcholine receptors (nAChRs) have been replicated , b-subunit (CHRNB2)].…”
Section: Introductionmentioning
confidence: 99%
“…ADNFLE was quickly recognized as a genetically heterogeneous disorder as most of the described families did not show mutations in the CHRNA4 gene [14,38], and new loci and genes were reported in the following years. In particular, a second locus was identified at chromosome 15q24 in one family [38] and a third locus spanning the pericentromeric region of chromosome 1 was identified in an Italian ADNFLE family [39], the latter containing the gene coding for the β2 subunit of the nACh receptor (CHRNB2) ( Table 1) [40]. Further CHRNB2 mutations were disclosed in different unrelated families and one sporadic case [41][42][43][44][45][46] (Table 1); in two families a coexistence of both epilepsy and specific deficits in tasks of verbal memory was observed [44,45]; in two patients ictal single-photon emission computed tomography showed a significant hyperperfusion of the cingulated gyrus [45].…”
Section: Genetic Forms Of Nflementioning
confidence: 99%
“…Many and early reports documented carbamazepine as the drug of choice in NFLE/ADNFLE patients [11,12,39,99], and basic studies of ADNFLE mutations suggested that mutated nAChR receptors demonstrate an increased sensitivity to carbamazepine [100].…”
Section: Treatmentmentioning
confidence: 99%